Substantiation of the use of spice plants for enrichment of wheat bread - Osokina, Nina; Kostetska, Kateryna; Gerasymchuk, Helena; Voziian, Valeriia; Telezhenko, Lyubov; Priss, Olesia; Zhukova, Valentina; Verkholantseva Valentуna; Palyanichka, Nadiya; Stepanenko Dmytrо (Eastern-European Journal of Enterprise Technologies, 2017)
Spice, aromatic, volatile-oil-bearing plants are rich in essential aromatic oils, vitamins, minerals that give phytoncidic, prophylactic, therapeutic, functional properties to products, improve food taste and digestibility. To prepare plant powder, it is necessary to use a certain part of plants, dry, grind in a laboratory mill to a particle size of 10-4–10-1 mm and mix to take a weighed prescription sample. In order to prepare the Quinoa flour, it is necessary to use Quinoa seeds, grind in a laboratory mill to a particle size of 30–40 microns and mix to take a weighed prescription sample. The use of plants in bread production is promising. The efficiency of using plants in the technology of bakery products as both an enhancer of nutrition value and a nutrient medium for yeast, which in turn affected the quality of finished products – porosity, acidity, specific volume was revealed. In order to develop an effective technology for the use of plant additives, create new types of products with the properties that meet today’s needs of consumers in Ukraine and the world, it is necessary to clarify the relationship between the components of spice plants and other components. The replacement of a part of the prescription amount of flour with dried and milled plants Narrowleaf Mountainmint (Piknanthemum trifolium L.), Quinoa (Chenopōdium quīnoa L.), Scarlet Beebalm (Monarda didyma L.), Korean Mint (Agastache rugosa L.), Hemp Dogbane (Vítex cannabinum L.), Mint-shrub (Elsholtzia Stauntonii L.), Moroccan Spearmint (Mentha spicаta Moroccan L.) during bread production was experimentally grounded and implemented. The developed method of bread production under the new formulations relates to the agriculture and food industry and can be applied during laboratory bread baking. The expediency of introducing an additive into the wheat dough in a dosage of not more than 5 % into the flour of Scarlet Beebalm powder; up to 10 % of Narrowleaf Mountainmint and Quinoa is revealed.